(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
In this study, the CR-39 solid nuclear track detector was used in order to know the effect of the irradiation time of Am-241 and P0-210 sources of alpha particles on the parameters of the CR-39 detector, with different times (1, 2, 3, 4, 5) h. The track density of alpha particles, average diameter, bulk etching rate, track etching rate, detector sensitivity, and etching efficiency were calculated. The highest values ​​were obtained at a time (5) h, so the value of the track density at radioactive source was polonium (739) track/mm², while it decreased at the radioactive source americium (451) track/mm², while the diameter average had the highest value at Am-241 is (2.544) µm, while its value decreased at Po-210 to reach (1.855) µm. The etching rate was (0.212) µm/h at Am-241 and (0.154) µm/h at Po-210, and the impact rate was (1.597) µm/h at Am-241 and (0.524) µm/h at Po-210. While the sensitivity of the commercial etching was at Am-241 (7.477) and at Po-210 (3.40), and finally the etching efficiency was (0.876) at Am-241 and (0.706) at Po-210.